Dampak Perubahan Iklim terhadap Keanekaragaman Hayati: Literature Review - Karmana, I Wayan (Biocaster : Jurnal Kajian Biologi, 2024)
Climate change is one of the biggest challenges faced by ecosystems and biodiversity worldwide. This research examines climate change's impact on biodiversity through a comprehensive literature review. By collecting and analyzing various previous studies, this research identifies patterns of change in flora and fauna species in response to changing climate variables, such as temperature, rainfall, and the frequency of extreme weather events. Literature results show that many species experience changes in distribution, behavior and reproductive timing, which have the potential to disrupt ecosystem interactions and damage ecological balance. This research also discusses the impact of climate change on natural habitats and the conservation efforts needed to protect biodiversity. These findings highlight the urgency of taking effective mitigation and adaptation measures to maintain biodiversity amidst the increasing challenges of climate change.